2022
DOI: 10.1038/s41598-022-16197-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extraction methods for a new source of biostimulant from Sargassum horneri on the growth of economically important red algae, Neopyropia yezoensis

Abstract: Sargassum horneri is a major bloom forming species in Korea and China. It is important to find a way to utilize the huge biomass of Sargassum horneri in the region. Seaweed-derived biostimulants are primarily derived from brown algae and are known to improve terrestrial crop growth and tolerance to abiotic stresses. Neopyropia yezoensis is the most important seaweed cultured species in Korea, and research is required to increase heat resistance as a solution against climate change. In this study, various extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…However, the molecular mechanism of heat-tolerance in N. yezoensis is still largely unknown. Our previous study reported that pre-treatment with SHE, a biostimulant extracted from Sargassum horneri, enhanced the heat-tolerance of N. yezoensis (Han et al, 2022). In the present study, we analyzed the transcriptomic regulation of heat-tolerance in N. yezoensis induced by SHE, which provided more information about heattolerance in N. yezoensis and the function of seaweed based biostimulants.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the molecular mechanism of heat-tolerance in N. yezoensis is still largely unknown. Our previous study reported that pre-treatment with SHE, a biostimulant extracted from Sargassum horneri, enhanced the heat-tolerance of N. yezoensis (Han et al, 2022). In the present study, we analyzed the transcriptomic regulation of heat-tolerance in N. yezoensis induced by SHE, which provided more information about heattolerance in N. yezoensis and the function of seaweed based biostimulants.…”
Section: Discussionmentioning
confidence: 93%
“…The clean thalli were then dried under 60°C and ground finely into powder using MM400 ball mill (Retsch, Germany). The biostimulant was prepared using the autoclaving method described in our previous study (Han et al, 2022). In brief, 8 g seaweed powder was added into 800 mL distilled water and stirred.…”
Section: Preparation Of Biostimulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, an acetone:ethanol extract of S. glaucescens rich in fucoxanthin caused a decrease in LPS-induced ROS and O 2 •− production in the same cell line at concentrations ranging from 25 µg/mL to 100 µg/mL [ 122 ]. The anti-inflammatory properties of fucoxanthin are further evidenced by in vivo studies in rodents [ 129 , 130 ], including scenarios of induced asthma [ 131 ] and induced colon inflammation [ 132 ].…”
Section: Bioactive Potential Of Sargassum Antioxidant Secondary Metab...mentioning
confidence: 99%
“…S. vulgare extracts were also reported to increase the germination of Triticum durum [ 181 ] and Phaseolus vulgaris [ 130 ] under salt stress. Regarding crop protection, Shahriari and coworkers [ 129 ] recently highlighted the potential of S. angustifolium extracts to the improvement of drought tolerance in Brassica napus L., while Han et al [ 131 ] remarked the positive effect of S. horneri extracts on the thermal tolerance of Neopyropia yezoensis algae. In a different approach, the treatment of Solanum lycopersicum with S. tenerrimum and S. fusiforme extracts was found to enhance its resistance to the fungi Macrophomina phaseolina, [ 132 ] and to reduce the late blight and gray mold diseases [ 182 ], respectively.…”
Section: Applications In Non-patented and In Patented Productsmentioning
confidence: 99%